Vertebral Fracture Identification - Bazzocchi, Alberto; Guglielmi, Giuseppe (Seminars in Musculoskeletal Radiology, 2016)
When bone becomes frail due to metabolic disorders, one or more vertebral fractures (VFs) may occur. A vertebral body fracture after minor trauma is a hallmark of osteoporosis. VFs represent a target in clinical practice and are often an endpoint in clinical trials. The health care and economic burden of VFs is huge, and they also significantly increase mortality and morbidity, as well as impairing function and quality of life. VFs are frequently clinically silent, thus imaging plays a role not only after symptoms appear but also in screening. A VF can be detected incidentally during imaging examinations performed for different clinical indications. A rapid look at the spine included in the scanned field may lead to the discovery of a VF, which must be reported because the event may change the management of the patient and prevent further problems, defusing the so-called vertebral fracture cascade. This review article focuses on VF awareness and identification to answer these questions: What is a VF? What is the impact of VFs? How can we detect VF?
Keywords: bone diseases metabolic; osteoporosis; osteoporotic fractures; spinal fractures; incidental findings